POTENSI EKSTRAK DAUN TERATAI (Nymphaea pubescens L.) DALAM MENGHAMBAT Staphylococcus aureus - Alfia Sabban; Dominggus Rumahlatu; Theopilus Watuguly (Program Studi Pendidikan Biologi FKIP Unpatti, 2017)
Background: The lotus (Nymphaea pubescens L.) is one of the ornamental plants that many people in demand because it has varieties, shapes, and color of flowers are diverse. The lotus has the potential to be developed as an antibacterial. This study aims to determine the use of lotus leaf extract as anti-bacterial Staphylococcus aureus. Method: This study included the making of extraction using maceration method using ethanol, phytochemical testing of lotus leaf extract and testing of anti bacterial activity was done by diffusion method agar by observing and measuring the inhibition zone diameter formed on Muller Hinton (MHA) media. Then done by giving lotus leaf extract with 3 treatment of concentration that is 5%, 10%, 20%, positive control (ampicillin) and negative control (aquades). With an incubation period of 1 x 24 hours. Result: The result of phytochemical test showed that lotus leaf extract contain alkaloid compound, triterpenoid, steroid, flavonoid, phenolic and saponin. Anti-bacterial activity test results showed that the concentration given was not able to inhibit the growth of test bacteria. Conclusions: Bacteriostatic tests with a 60% extract concentration indicating that at 10-5 to 10-9 dilutions there were no bacterial colonies growing.